L’écriture de la nature chez Barry Lopez : enjeux et stratégies - Yves-Charles Grandjeat (Anglophonia)
This paper examines how ecocentric writing in general and, in particular, the work of Barry Lopez negotiate the tension between the need and the desire to write about nature, on the one hand and, on the other, the commitment to respect and protect nature’s fundamentally alien character from symbolic gestures of encroachment or appropriation by the writer himself. This leads to an investigation of Lopez’s politics and rhetorics of negative presentation, which fully registers how nature resists language and representation. Further, this paper draws attention to the strategic use of comparison in Lopez’s representational ethics, arguing that unexpected comparisons enable him to foreground the artificiality of his own stance, while distancing himself from any romantic claim to merge with nature, thus clarifying his own position as a committed and respectful outsider.